In-situ defect detection and material property evaluationin additive manufacturing using acoustic signal and machinelearning - Abdullah Bin Zainal; Zheng Jie Tan; Saritha Samudrala; Zi Wen Tham; Lei Zhang; Santhakumar Sampath (e-Journal of Nondestructive Testing)
In-situ monitoring is crucial for detecting defects and